Heat dissipation member and manufacturing method thereof
The laminated heat dissipation member, with a carbon material and metal layers bonded on both sides, addresses the challenge of maintaining thermal conductivity and durability under heat cycles, effectively preventing interface peeling and bonding defects.
Patent Information
- Application Number
- JP2020154844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-15
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2040-09-15
AI Technical Summary
Existing heat dissipation members for semiconductor devices face challenges in maintaining durability and thermal conductivity when subjected to repeated thermal stresses from heat cycles, leading to issues like cracking and peeling at the interface between metal and carbon materials.
A laminated heat dissipation member is developed, featuring a carbon material with specific gas permeability properties and a metal material, such as aluminum or copper, bonded on both sides of the carbon. This structure prevents direct integration of metals and maintains a high area ratio of carbon material, ensuring excellent bonding and thermal conductivity.
The proposed heat dissipation member exhibits excellent durability and maintains high thermal conductivity even after exposure to heat cycles, significantly reducing the occurrence of bonding defects and interface peeling.
Smart Images

Figure 0007659377000007 
Figure 0007659377000008 
Figure 0007659377000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat dissipation member suitable for semiconductor devices such as power modules, and a manufacturing method thereof. Here, the heat dissipation member is a heat transfer member for transferring heat generated from a heat generating body such as a semiconductor element to a cooling medium (air, liquid), a housing, etc. [Background technology]
[0002] Semiconductor elements used in power modules are usually mounted on an insulated circuit board, which is a ceramic plate with metal plates bonded to both sides. A heat dissipation base (heat transfer member such as a metal base plate) made of a metal material is generally placed on the rear side of the insulated circuit board where the semiconductor elements are mounted, and a heat dissipation structure is constructed by integrating the heat dissipation base and the insulated circuit board. Such heat dissipation structures require ingenuity to prevent deformation caused by the difference in thermal expansion between ceramics and metals, and the occurrence of joint defects (cracks, peeling, void formation, etc.) between the components due to thermal stress.
[0003] Patent Document 1 describes a technique for using a metal plate made of copper or a copper alloy with a Vickers hardness of 40 to 60 as a metal plate for fixing a heat sink that constitutes a metal-ceramic bonded substrate (insulated circuit substrate). This effectively prevents cracks from occurring in the solder or ceramic substrate, even if Pb-free solder is used to fix the heat sink (metal base plate) to the metal plate for fixing the heat sink. However, there is a problem in that cracks cannot be sufficiently prevented from occurring in the ceramic substrate when a heat cycle is applied.
[0004] Patent Document 2 describes a heat transfer member in which the surface of a carbon plate is covered with a metal casting. A graphene laminate is used as the carbon plate. Graphene is brittle, so there is a problem that the thermal resistance at the bonding interface with the metal increases, resulting in a decrease in thermal conductivity as a heat transfer member (paragraphs 0004 and 0007). However, according to the technology of Patent Document 2, the casting body comes into surface contact with the surface of the carbon plate, and the casting body presses the surface of the plate due to the difference in the amount of contraction between the casting body and the plate when the casting body is formed, so that the adhesion is increased and the thermal conductivity of the composite heat transfer member can be improved (paragraphs 0011, 0012, and 0050). In addition, the casting body and the carbon plate each have residual stress, and even when used at a high temperature of about 150°C, the residual stress is not lost even if it becomes small, so the casting body continues to press the surface of the carbon plate (paragraphs 0051 and 0052). However, the technology disclosed in Patent Document 2 leaves room for improvement in terms of durability against reduction in bonding strength and peeling at the interface between the cast body and the carbon plate (graphene laminate) when subjected to a heat cycle.
[0005] Patent Document 3 describes the use of a stress relaxation plate made of a composite material in which a porous sintered carbon body is impregnated with aluminum or its alloy as an intermediate plate bonded to the front and back of a ceramic plate in an insulating circuit board on which a semiconductor element is mounted. As the porous sintered carbon body, for example, a commercially available artificial graphite material (density 1.85 g / cm 3 , porosity 12vol%, bending strength 3.5kg / cm 2 , thermal conductivity 100W / m K, thermal expansion coefficient 3.8×10 -6 / ℃) can be cut out and used (paragraph 0040). Patent Document 4 also describes a heat sink material in which the adhesion between a porous sintered body and a metal is improved by impregnating a porous sintered body made of carbon or graphite with a metal. However, it has been found that composite materials using these porous carbons may be prone to a decrease in thermal conductivity when subjected to a heat cycle. The reason for this is that the strength of the porous sintered body of carbon is low, and therefore voids and peeling are likely to occur due to repeated thermal stress caused by the heat cycle at the contact surface with the impregnated metal or the contact surface with the metal film covering the periphery. In addition, in the case of a porous carbon body, high temperature and high pressure are required to fully fill the inside of the pores with metal, making it difficult to manufacture a carbon-metal composite that maintains sufficient thermal conductivity and strength.
[0006] Patent documents 5 to 7 describe techniques for alleviating the thermal expansion of a metal base plate by providing a rod- or plate-shaped reinforcing material with a small thermal expansion coefficient inside the base plate. However, even with these techniques, repeated heat cycles can cause problems with bonding defects between the base plate parent metal and the reinforcing material, and there is still room for improvement. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2006-282417 A [Patent Document 2] JP 2019-96858 A [Patent Document 3] International Publication No. 2008 / 093808 [Patent Document 4] JP 2006-298687 A [Patent Document 5] JP 2011-77389 A [Patent Document 6] JP 2012-199452 A [Patent Document 7] JP 2014-82466 A Summary of the Invention [Problem to be solved by the invention]
[0008] Carbon materials have a thermal expansion coefficient close to that of ceramics and good thermal conductivity, making them useful as constituent materials for heat dissipation members to be bonded to insulating circuit boards using ceramics. However, as described above, there has been a need for improvement in durability when repeated thermal stress due to heat cycles is applied. The present invention aims to provide a highly durable heat dissipation member that can maintain good thermal conductivity even when subjected to a heat cycle, i.e., when exposed to a severe thermal stress environment in which rapid fluctuations in thermal stress due to repeated temperature increases and decreases are applied, in a composite material using a metal and a carbon material. [Means for solving the problem]
[0009] The above object can be achieved by a heat dissipation member having a laminated structure in which a metal material and a carbon material having the properties shown in (A) below are bonded together. (A) When a pressure of 200 kPa of nitrogen gas is applied to one main surface of a plate-shaped sample having a thickness of 11 mm and made of the carbon material, the flow rate of the nitrogen gas penetrating to the other main surface side is 0.01 m2 over the area of the main surface being pressurized. 2 Carbon material with gas permeability of 5 L / min to 30 L / min per unit area, provided that the area of the main surface to be pressurized is 0.005 m 2 That is all. Here, the "principal surface" refers to the surface at the end of the plate in the thickness direction. A plate has two opposing principal surfaces.
[0010] The carbon material is preferably a graphitized material formed by cold isostatic pressing (CIP). The strength of the carbon material is preferably a bending strength of 40 MPa or more. The metal material constituting the laminated structure is preferably any one of aluminum, aluminum alloy, copper, and copper alloy.
[0011] The laminated structure is preferably a laminated structure in which a metal material is bonded to both sides of a carbon material. In this case, the two metal materials sandwiching the carbon material can be members separated from each other. That is, it is not necessary to adopt a so-called "cast-in" structure in which the carbon material is enclosed inside the metal material, or a structure in which the two metals sandwiching the carbon material are directly connected somewhere and integrated. When a structure in which the two metal materials sandwiching the carbon material are separated from each other is applied, it is preferable that the area ratio of the carbon material-containing region in the region where the metal materials on both sides sandwiching the carbon material overlap is 90% or more in the projected area viewed in the stacking direction. A plating layer may be formed on the surface of the metal material bonded to the carbon material.
[0012] Examples of the joining form between the metal material and the carbon material include a structure in which the molten metal of the metal material is solidified on the surface of the carbon material, and a structure in which the metal material and the carbon material are joined by a brazing method.
[0013] The heat dissipation member of the present invention may be a heat dissipation structure including a heat transfer member such as a ceramic material, so long as it has a laminated structure in which a metal material and a carbon material having the properties shown in (A) above are bonded. Examples of the heat dissipation member of the present invention including a ceramic material include a heat dissipation base in which a metal material and a carbon material having the properties shown in (A) above are bonded to an insulating circuit board in which a heat dissipation side metal material, a ceramic, and a circuit metal material are laminated and integrated in the above order. In addition, examples of heat dissipation structures include a type in which a ceramic material is directly bonded to the surface of a metal material bonded to a carbon material on the opposite side to the carbon material to form an insulating circuit board. In any of these types, when metal materials are bonded to both sides of a carbon material, it is sufficient that a ceramic material is disposed on the surface of either one of the metal materials on the opposite side to the carbon material. The circuit metal material is intended to mount a semiconductor element to form a circuit. The above-mentioned "heat dissipation base" and "insulating circuit board" can be bonded via a brazing material layer, a solder layer, or a metal sintered layer.
[0014] As a method for manufacturing the heat dissipation member in which a carbon material and a metal material are joined, the following techniques can be applied depending on whether the carbon material and the metal material are joined by "molten metal joining" or "brazing". [In the case of molten metal joining] A method for manufacturing a heat dissipation member, comprising the steps of: injecting molten aluminum or an aluminum alloy into a mold in which a carbon material having the properties shown in (A) above is placed, filling the space in the mold with the molten metal, and then solidifying the molten metal to form a laminated structure in which a metal material made of aluminum or an aluminum alloy and the carbon material are bonded together. [By soldering] A method for producing a heat dissipation member, comprising: a step of joining a metal material and a carbon material having the properties shown in (A) above by a brazing method to form a laminated structure in which the metal material and the carbon material are joined. Effect of the Invention
[0015] According to the present invention, a heat dissipation member with excellent durability and with very little deterioration in thermal conductivity when subjected to a heat cycle can be realized by using a carbon material with good thermal conductivity and a thermal expansion coefficient close to that of ceramics. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a schematic diagram illustrating a cross-sectional structure of a heat dissipation member according to the present invention in which a heat dissipation base and an insulating circuit board are joined together. [Diagram 2] FIG. 2 is a schematic diagram illustrating a cross-sectional structure of a heat dissipation member according to the present invention, in which an insulating circuit board is formed by directly bonding a ceramic material to a metal material that is bonded to a carbon material. [Diagram 3] FIG. 13 is a schematic diagram illustrating a cross section of a mold for manufacturing the “heat dissipation base” portion by the molten metal joining method. [Figure 4] FIG. 2 is a schematic cross-sectional view of a mold for producing a "base-integrated insulating circuit board" by a molten metal bonding method. [Diagram 5]FIG. 1 is a schematic diagram illustrating a cross section of a mold having fin-forming recesses for producing a "base-integrated insulated circuit board" having heat dissipation fins by a molten metal bonding method. [Figure 6] FIG. 13 is a diagram illustrating a cross section of a laminate in which a metal material and a carbon material constituting a heat dissipation base are joined by a brazing method. [Figure 7] FIG. 2 is a schematic cross-sectional view of a jig for restraining a carbon material when measuring the gas permeability of the carbon material. [Figure 8] FIG. 1 is a schematic diagram showing the cross-sectional structure of the heat dissipation base product under test. [Figure 9] FIG. 2 is a schematic diagram showing the cross-sectional structure of a heat dissipation member consisting of a heat dissipation base and an insulating circuit board as a test specimen. [Figure 10] FIG. 2 is a schematic diagram showing the cross-sectional structure of a heat dissipation member made of a base-integrated insulating circuit board product as a test specimen. [Figure 11] FIG. 2 is a schematic diagram showing the cross-sectional structure of a heat dissipation member made of a base-integrated insulating circuit board product as a test specimen. [Figure 12] 4A and 4B are a side view and a plan view for explaining a method for measuring the thermal conductivity of a test specimen (single heat dissipation base). [Figure 13] 4A and 4B are a side view and a plan view for explaining a method for measuring the thermal resistance of a test specimen. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] FIG. 1 shows a schematic cross-sectional structure of a heat dissipation member according to the present invention in which a heat dissipation base and an insulating circuit board are bonded together. A heat dissipation base 100 and an insulating circuit board 200 are bonded together via a bonding metal layer 50. The bonding metal layer 50 is a brazing material layer, a solder layer, a metal sintered layer, or the like. The insulating circuit board 200 has a circuit metal material 41 on one side of a ceramic material 30 and a heat dissipation side metal material 42 on the other side. A semiconductor element of a power module is mounted on the circuit metal material 41. In order to dissipate heat from the semiconductor element, which is a heat generating body, ceramics with good thermal conductivity such as aluminum nitride, ceramics with high strength such as silicon nitride, and inexpensive ceramics such as alumina are often used for the ceramic material 30, and metals with high thermal conductivity mainly made of Al or Cu are used for the circuit metal material 41 and the heat dissipation side metal material 42. Representative products of the insulating circuit board 200 include an "aluminum-clad ceramic circuit board" having an aluminum-ceramic-aluminum laminated structure, and a "copper-clad ceramic circuit board" having a copper-ceramic-copper laminated structure.
[0018] The heat dissipation base 100 is a heat transfer member for transferring heat from the insulating circuit board 200 to a heat sink or other heat dissipating body, and is also a fixing member for installing the insulating circuit board 200 in a housing. In the example of FIG. 1, a carbon material 10 is used as a constituent material of the heat dissipation base 100. This heat dissipation base 100 has a laminated structure in which metal materials 21 and 22 are bonded to both sides of the carbon material 10. The carbon material 10 and the metal materials 21 and 22 are bonded by solidifying a molten metal of the metal material on the surface of the carbon material 10, or are bonded by brazing. The carbon material has a thermal expansion coefficient close to that of ceramics and has good thermal conductivity. Since the carbon material 10 is tightly bonded to the metal materials 21, 22, the difference in thermal expansion between the heat dissipation base 100 portion and the insulating circuit board 200 portion can be kept small, thereby preventing problems such as local deformation of the heat dissipation member formed by integrating the heat dissipation base 100 and the insulating circuit board 200 (e.g., warping of the heat dissipation base 100) and damage to the bonding metal layer 50 (e.g., cracking or peeling).
[0019] FIG. 2 shows a schematic cross-sectional structure of a heat dissipation member according to the present invention, in which a ceramic material is directly bonded to a metal material bonded to a carbon material to form an insulating circuit board. The heat dissipation member has a laminated structure in which a carbon material 10 is bonded to metal materials 21 and 22. The carbon material 10 and the metal materials 21 and 22 are bonded by solidifying the molten metal of the metal material on the surface of the carbon material 10, or by brazing. A ceramic material 30 is directly bonded to the surface of the metal material 21 opposite to the carbon material. A circuit metal material 41 for mounting a semiconductor element of a power module is bonded to the ceramic material 30. The heat dissipation base 100, which is composed of the carbon material 10 and the metal materials 21 and 22 on both sides of the carbon material 10, constitutes an insulating circuit board 300 together with the ceramic material 30 and the circuit metal material 41. Hereinafter, this type of heat dissipation structure may be referred to as a "base-integrated insulating circuit board." In this case too, since the carbon material 10 is tightly bonded to the metal materials 21, 22, the difference in thermal expansion between the heat dissipation base 100 portion and the ceramic material 30 portion can be kept small, preventing problems such as local deformation of the insulating circuit board 300 and damage to the ceramic material 30.
[0020] 1 and 2, the exposed metal surface may be plated with Ni, Ni alloy, Au, or the like, as necessary. A heat sink such as fins may be provided on the metal material 22 on the side opposite to the carbon material 10. The surface of the metal material 22 on the side opposite to the carbon material 10 may be cooled by a cooler using a liquid cooling medium.
[0021] In a heat dissipation member in which metal materials 21 and 22 are bonded to both sides of a carbon material 10, such as the heat dissipation base 100 portion shown in FIG. 1 and FIG. 2, the metal materials 21 and 22 sandwiching the carbon material 10 can be configured as members separated from each other. Separated from each other means that the metal materials located on both sides of the carbon material are not integrated at the time of casting, and the metal surfaces of both are not in direct contact with each other. In the heat dissipation member of the present invention, since the bonding strength between the carbon material 10 and the metal materials 21 and 22 is high, such metal materials can also be sandwiched between the carbon material to form a "metal-carbon-metal" sandwich structure. In addition, when a laminated structure of the metal material 21, the carbon material 10, and the metal material 22 is obtained by the "brazing method" described later, it is also possible to sandwich a carbon material having an area smaller than that of the metal material. However, from the viewpoint of ensuring sufficient thermal conductivity between the metal materials 21 and 22, it is preferable that the area ratio of the carbon material-containing region within the region where the metal materials on both sides of the carbon material overlap in the projected area viewed in the stacking direction (the z-axis direction shown in Figures 1 and 2) be 90% or more.
[0022] [Carbon materials] In the present invention, the carbon material that forms a laminated structure with a metal material has the following properties (A). (A) When a pressure of 200 kPa of nitrogen gas is applied to one main surface of a plate-shaped sample having a thickness of 11 mm and made of the carbon material, the flow rate of the nitrogen gas penetrating to the other main surface side is 0.01 m2 over the area of the main surface being pressurized. 2 Carbon material with gas permeability of 5 L / min or more per unit area, provided that the area of the main surface to be pressurized is 0.005 m 2 That is all. The plate thickness is 11 mm, and the area of the main surface to be pressed is 0.005 m 2 By doing so, the measurement accuracy is improved and the differences between materials can be clearly understood. If the plate thickness is too large, the pressure must be increased, and the equipment becomes large, so a sample plate thickness of 11 mm was adopted as a necessary and sufficient thickness.
[0023] The inventors used various carbon materials to fabricate heat dissipation members having a laminated structure in which a metal material and a carbon material were bonded, and investigated the change behavior of thermal conductivity (thermal conductivity or thermal resistance) when a heat cycle was applied. As a result, as shown in (A) above, for the carbon material bonded to the metal material, the flow rate of nitrogen gas passing through a plate thickness of 11 mm at a pressure of 200 kPa was 100% when the pressure area was 0.01 m. 2 It was found that the use of a material having a gas permeability of 5 L / min or more per unit time is extremely effective in maintaining thermal conductivity when subjected to a heat cycle.
[0024] Observation of the bonded interface between the metal material and the carbon material after the heat cycle test revealed that the occurrence of bond defects such as voids and peeling was significantly suppressed in the heat dissipation component using the above-mentioned gas-permeable carbon material. It is believed that a tight bond was achieved between the above-mentioned gas-permeable carbon material and the metal material, which significantly improved the durability of the bonded interface against repeated thermal stress caused by heating and cooling. As a result, high thermal conductivity was maintained at the bonded interface after the heat cycle load.
[0025] Even if the bulk density of carbon materials is the same, their gas permeability differs depending on their pore structure. Carbon materials contain both closed pores and pores that form continuous pores, and it is generally believed that pore structures with many continuous pores have high gas permeability. When the pore structure has a relatively high level of gas permeability, the anchor effect caused by the impregnation of metal materials and brazing filler metal is exerted, resulting in high joint strength between the metal material and the carbon material. The pressure of 200 kPa of pressure permeating through a plate thickness of 11 mm and a pressure area of 0.01 m2 is an index of the gas permeability of carbon materials. 2 The flow rate of nitrogen gas per unit time is preferably 5 L / min or more, and more preferably 10 L / min or more.
[0026] However, in terms of durability of the bonded interface when subjected to a heat cycle, the higher the gas permeability of the carbon material, the more advantageous it is. If gas permeability is too high, and measures are not taken to sufficiently remove gas components such as oxygen remaining in the gaps when bonding metal materials, such residual gas components are likely to cause voids at the bonded interface. In addition, carbon sintered bodies with excessively high gas permeability can also be disadvantageous in terms of durability when subjected to a heat cycle due to their low strength. As a result of various studies, in the present invention, it was determined that a pressure of 200 kPa permeates a plate thickness of 11 mm at a pressure area of 0.01 m 2 The carbon material used has a nitrogen gas flow rate of 30 L / min or less per unit time. It may be possible to use a carbon material with a flow rate of 25 L / min or less. The porous carbon and the porous sintered carbon bodies used in the above-mentioned prior art documents have a pressure of 200 kPa that penetrates a plate thickness of 11 mm and has a pressurized area of 0.01 m. 2 When the nitrogen gas flow rate per unit area was measured, it far exceeded 30 L / min, and therefore cannot be applied to the present invention.
[0027] The carbon material applied to the present invention is desirably high strength. For example, a carbon material having a bending strength of 40 MPa or more is desirable, more preferably 45 MPa or more, and even more preferably 48 MPa or more. Here, the bending strength can be a three-point bending strength measured in accordance with JIS R7222:1017. A square timber sample of 20 mm x 20 mm x 100 mm can be applied as a test piece for measuring bending strength. The use of a high-strength carbon material is advantageous in ensuring excellent durability at the joint interface with a metal material. In addition, it is desirable to use a high-strength carbon material when constructing a heat dissipation member in which both metal materials sandwiching a carbon material are composed of members spaced from each other. When the carbon material is thin or the metal material to be joined is thin, it is more preferable to use a carbon material having a bending strength of 55 MPa or more, or even 60 MPa or more, in order to ensure the strength as a heat dissipation member. The bulk density of the carbon material is 1.80 to 1.90 g / cm 3 It is more preferable that:
[0028] An example of an industrial product suitable for the carbon material applied to the present invention is a CIP (cold isostatic press) graphitized material. This is isotropic graphite produced by a process in which graphite raw material is CIP molded and then graphitized. CIP graphitized material has isotropic thermal conductivity and mechanical properties, and is a material that can achieve a bending strength level of 40 MPa or more when it exhibits the above-mentioned gas permeability specified in the present invention. The properties of carbon materials, such as gas permeability, bending strength, and bulk density, reflect differences in structure that depend on various manufacturing conditions, such as the particle size of the carbon raw material and the blending of auxiliary agents.
[0029] In addition, the thinner the carbon material, the better its thermal conductivity, but if it is too thin, it is difficult to handle and is prone to cracking during molten metal joining or brazing. On the other hand, if it is too thick, it is disadvantageous in terms of miniaturization of the heat dissipation member. As a result of various studies, the thickness of the carbon material applied to the present invention is preferably 0.1 to 5 mm, more preferably 0.5 to 4 mm, and even more preferably 1 to 3 mm. A specific form of the carbon material constituting the heat dissipation member of the present invention can be a plate material (carbon plate) made of a carbon material having the above-mentioned properties. For example, a plate material cut out from a product (e.g., a graphite block product) of a carbon material having the above-mentioned properties can be used. A plate material obtained by a method of thinning by cutting using a milling machine or the like is also included in the above-mentioned "cut out plate material".
[0030] [Metal materials] As the metal material to be bonded to the carbon material to form the heat dissipation member according to the present invention, it is preferable to use any one of aluminum, aluminum alloys, copper, and copper alloys, which have excellent thermal conductivity. Examples of aluminum-based materials include pure aluminum (purity of 99.9% or more), alloy number A1050 (purity of 99.5% or more), Al-0.4Si-0.05B alloy, Al-0.05Mg-0.04Si alloy, Al-0.08Mg-0.06Si alloy, Al-0.1Zr alloy, Al-0.2Zr alloy, Al-0.1Zn alloy, and Al-0.2Zn alloy. In the case of copper-based materials, pure copper-based materials such as alloy number C1020 (oxygen-free copper) and alloy number C1100 (tough pitch copper) are suitable. As for the properties of the above-mentioned metal material, it is particularly preferable that the thermal conductivity is 170 W / (m·K) or more and the 0.2% proof stress is 40 MPa or less.
[0031] [Joint structure of metal and carbon materials] In order to realize a tight joint having excellent durability between a metal material and the above-mentioned gas permeable carbon material, it is effective to employ either of the joint structures (i) or (ii) shown below. (i) A structure in which a molten metal material is solidified while in contact with the surface of a carbon material. (ii) A structure in which a metal material and a carbon material are joined by the principle of brazing All of these joint structures are formed by solidifying molten metal on the surface of the carbon material. When the molten metal comes into contact with the surface of the carbon material, the microscopic adhesion area between the metal and the carbon material increases, and an excellent anchor effect is exhibited. However, in order to ensure excellent durability when subjected to a heat cycle, it is a prerequisite that the metal is combined with a carbon material that exhibits a predetermined gas permeability, as described above.
[0032] [Manufacturing method] The heat dissipation member having the above joint structure (i) can be manufactured by the "molten metal joining method," and the heat dissipation member having the above joint structure (ii) can be manufactured by the "brazing method." Examples of these methods are given below.
[0033] [Molt metal joining method (1)] FIG. 3 shows a schematic cross-section of a carbon mold for manufacturing a "heat dissipation base" having a laminated structure in which a metal material and a carbon material are bonded by a molten metal bonding method. A plate-shaped carbon material 10 is held inside a carbon mold 1 made by combining an upper mold member 1a and a lower mold member 1b. To hold the plate-shaped carbon material 10 in the internal space of the mold 1, for example, a notch step is provided in a part of the surface of each of the upper mold member 1a and the lower mold member 1b that abuts against the mating mold member so that a groove having a width corresponding to the thickness of the carbon material 10 is formed at the abutting portion of the inner surface of the mold 1 when the upper and lower mold members are abutted and tightly attached, and the carbon material 10 is sandwiched between the upper and lower mold members at the cutout step portion. In the example of FIG. 3, the carbon material 10 is sandwiched at the abutting portion of the upper mold member 1a and the lower mold member 1b on the back side and the front side as viewed in the projection direction (y-axis direction) of this cross-sectional view.
[0034] The mold 1 is placed in a heating furnace and heated in an atmosphere of a non-oxidizing gas such as nitrogen gas, and a molten metal material melted in a melting furnace (not shown) is poured into the mold 1 through a pouring port 4 of a cover member 3 installed in an upper mold member 1a. At this time, it is preferable that the molten metal to be poured is in a state in which the oxide film on the surface of the molten metal has been removed. For example, it is preferable to pour the molten metal while performing an oxide film removal process on the molten metal supplied from the melting furnace. As the oxide film removal process, in the case of molten metal of an aluminum-based metal, for example, a method of pouring the molten metal while removing the oxide film on the surface of the molten metal by passing it through a very small nozzle is effective. The molten metal 2 stored in the molten metal reservoir 51 in the mold 1 is transferred to the molten metal supply path 52, and the molten metal 2 is allowed to reach the tip of the space surrounding the carbon material 10 (the left end in the x-axis direction in FIG. 3). A water-cooled copper block is brought into contact with the outer wall of the mold at the tip to remove heat, and the molten metal 2 is directionally solidified from the tip. At this time, in order to ensure that the molten metal 2 reaches the tip of the mold without any gaps and to prevent shrinkage cavities due to solidification shrinkage of the metal, the molten metal 2 is poured and solidified while being pressurized with an inert gas such as nitrogen gas at a pressure of, for example, 30 to 200 kPa from a pouring port 4.
[0035] Since the molten metal 2 solidifies while being sufficiently in close contact with the surface of the carbon material 10, a tight bond is realized at the interface between the metal material and the carbon material 10 formed by solidifying the molten metal 2. After the molten metal 2 has completely solidified in all areas of the mold, it is cooled to room temperature, the carbon mold 1 is dismantled, and the solidified mass in which the carbon material 10 is embedded is taken out. The solidified portion of the molten metal 2 remaining in the molten metal reservoir 51 and the molten metal supply passage 52 is separated from the solidified mass. In addition, the ears of the carbon material 10 that are protruding from the metal material in the portion that was sandwiched between the upper and lower mold members are also cut and removed. In this way, a heat dissipation base portion having a laminated structure as shown by the reference numeral 100 in FIG. 1 can be obtained. If necessary, polishing may be performed to smooth the surface of the metal material or to remove deposits from the mold.
[0036] [Molt metal joining method (2)] FIG. 4 shows a schematic cross-section of a carbon mold for manufacturing a "base-integrated insulating circuit board" having a laminated structure in which a metal material and a carbon material are bonded by a molten metal bonding method. A plate-shaped carbon material 10 and a plate-shaped ceramic material 30 are held inside a carbon mold 1 made by combining an upper mold member 1a and a lower mold member 1b. The plate-shaped carbon material 10 can be held in the mold 1 by, for example, sandwiching it between the upper and lower mold members as in the case of FIG. 3. In the example of FIG. 4, the carbon material 10 is also sandwiched at the contact portions of the upper mold member 1a and the lower mold member 1b on the far and near sides as viewed in the projection direction (y-axis direction) of this cross-sectional view. To hold the plate-shaped ceramic material 30 at a predetermined height in the mold 1, for example, a pedestal (not shown) for supporting the edge of the ceramic material 30 that does not form the metal material for circuits and restraining the ceramic material 30 from moving horizontally can be provided at the bottom of the lower mold member 1b, and the ceramic material 30 can be placed on the pedestal. In this case, a gap corresponding to the thickness of the metal material for circuits is formed between the bottom of the lower mold member 1b and the ceramic material 30 so as to communicate with the molten metal supply passage 52. In the example of FIG. 4, the pedestals are provided at the back and front sides as viewed in the projection direction (y-axis direction) of this cross-sectional view.
[0037] The mold 1 is placed in a heating furnace and heated in an atmosphere of a non-oxidizing gas such as nitrogen gas, and a molten metal material melted in a melting furnace (not shown) is poured into the mold 1 from the pouring port 4 of the cover member 3 installed in the upper mold member 1a. At this time, it is preferable that the molten metal to be poured is in a state in which the oxide film on the surface of the molten metal has been removed. For example, it is preferable to pour the molten metal while performing an oxide film removal process on the molten metal supplied from the melting furnace by the method described above. The molten metal 2 stored in the molten metal reservoir 51 in the mold 1 is transferred to the molten metal supply path 52, and the molten metal 2 is allowed to reach the tip of the space surrounding the carbon material 10 and the ceramic material 30 (the left end in the x-axis direction in FIG. 4). A water-cooled copper block is brought into contact with the outer wall of the mold at the tip to remove heat, and the molten metal 2 is directionally solidified from the tip. At this time, in order to ensure that the molten metal 2 reaches the tip of the mold without any gaps and to prevent shrinkage cavities due to solidification shrinkage of the metal, the molten metal 2 is poured and solidified while being pressurized with an inert gas such as nitrogen gas at a pressure of, for example, 30 to 200 kPa from a pouring port 4.
[0038] As in the case of FIG. 3, a tight bond is realized at the interface between the metal material formed by solidifying the molten metal 2 and the carbon material 10. In addition, sufficient bond strength is ensured at the interface between the metal material formed by solidifying the molten metal 2 and the ceramic material 30. After the molten metal 2 has completely solidified in all areas of the mold, it is cooled to room temperature, the carbon mold 1 is dismantled, and the solidified mass in which the carbon material 10 and the ceramic material 30 are embedded is taken out. The solidified portion of the molten metal 2 remaining in the molten metal reservoir 51 and the molten metal supply path 52 is cut off from the solidified mass. In addition, the ears of the carbon material 10 that were sandwiched between the upper and lower mold members and that protrude from the metal material are also cut and removed. Furthermore, after polishing the surfaces of the metal material and the metal material for the circuit as required, in order to remove unnecessary metal covering the vicinity of the end of the ceramic material 30 and to form a circuit pattern on the surface of the ceramic material 30 opposite to the carbon material 10, a predetermined portion is masked and then an etching solution such as iron chloride is sprayed to dissolve and remove a part of the metal material on the surface of the ceramic material 30. In this manner, a base-integrated insulating circuit board having a laminated structure as shown by reference numeral 300 in FIG. 2 can be obtained. Thereafter, the surface of the base-integrated insulating circuit board can be subjected to electroplating such as Ni plating, electroless Ni-P plating, electroless Au plating, etc. as required.
[0039] As shown in FIG. 5, by providing a fin-forming recess 53 in the upper mold member 1a, it is possible to obtain a base-integrated insulating circuit board in which a heat sink having heat dissipating fins is directly bonded to the carbon material 10.
[0040] [Brazing method] In the brazing method, a laminate in which a metal material and a carbon material are laminated via a brazing material component is heated to a temperature below the melting point of the metal material while a predetermined pressure is applied to the lamination interface, and the surface of the metal material near the lamination interface is melted together with the brazing material component, thereby joining the metal material and the carbon material. In brazing, a filler metal previously adjusted to a low-melting point alloy composition such as a eutectic composition is often used as the brazing material. However, since aluminum and copper are easily made to have low melting points by forming a binary alloy, in the present invention in which surface joining is sufficient, a method is preferable in which a filler metal is not used and elements that form a low-melting point binary alloy are diffused from the surface of the metal material to lower the melting point near the surface. In this case, the low-melting point alloy formed near the surface functions as the "brazing material" instead of the filler metal.
[0041] FIG. 6 illustrates a cross section of a laminate in the case where the metal material and the carbon material constituting the heat dissipation base are joined by a brazing method. A plurality of laminates 101, each having metal materials 21 and 22 arranged above and below the carbon material 10, are stacked, separated by a spacer 5 made of a refractory material such as ceramics or a carbon material. In FIG. 6, two sets of laminates 101 are stacked, but a plurality of laminates 101 may be stacked on the top spacer 5. A film of a brazing material component element is previously deposited by a sputtering method or the like on the surface of each of the metal materials 21 and 22 to be joined to the carbon material. A film of a brazing material component is interposed at the "metal-carbon interface" indicated by the symbol A in FIG. 6. As the brazing material component element, Si, Cu, Ag, Ge, etc. are suitable when the metal materials 21 and 22 are aluminum-based metals, and P, Ag, Sn, etc. are suitable when the metal materials 21 and 22 are copper-based metals. The laminate is placed in a vacuum furnace, the pressure in the furnace is reduced, a load is applied in the lamination direction (z-axis direction shown in FIG. 6), and the laminate is heated and maintained at a predetermined temperature lower than the melting points of the metal materials 21 and 22, causing the brazing material component elements to diffuse into the metal materials 21 and 22. As the diffusion progresses and an alloy is formed between the component elements (Al or Cu) of the metal materials 21 and 22 and the brazing material component elements near the lamination interface, the liquidus temperature near the surfaces of the metal materials 21 and 22 decreases in response to the change in the alloy composition, and a molten metal phase is generated at the lamination interface (metal-carbon interface). This molten metal phase solidifies while being sufficiently in close contact with the surface of the carbon material 10, so that a tight bond is realized at the interface between the metal materials 21 and 22 and the carbon material 10.
[0042] The laminate 101 obtained by brazing can be used as a heat dissipating member constituting a part of the heat dissipating base 100 shown in Fig. 1. When the heat dissipating base 100 and the insulating circuit board 200 shown in Fig. 1 are joined by a brazing method using a sputtering film of the brazing material component elements as described above, instead of by the joining metal layer 50, brazing of the "metal-carbon interface" that forms the part of the heat dissipating base 100 and brazing of the "metal-metal interface" that joins the heat dissipating base 100 and the insulating circuit board 200 can be performed simultaneously. EXAMPLES
[0043] [Gas permeability test of carbon materials] The carbon materials (all CIP graphitized materials) shown in Table 1 were prepared. Carbon material No. C1 is a product name MC4422, C2 is MC4415, C3 is MC4423, C4 is MC4416, C5 is MC4319, C6 is MC4509, and C7 is MC4313, all manufactured by Mechanical Carbon Kogyo Co., Ltd. The gas permeability of these carbon materials was examined as follows. FIG. 7 shows a schematic cross section of a jig for restraining a carbon material when measuring the gas permeability of the carbon material. This jig is composed of a gas inlet plate 61 and a gas outlet plate 62 made of stainless steel. A plate-shaped carbon material 10 having a thickness of 11 mm, which is a measurement sample, is placed in a recess provided in the gas inlet plate 61, and the gas inlet plate 61 and the gas outlet plate 62 are fastened with a plurality of bolts (not shown). The carbon material 10 is restrained by pressing one of the main surfaces of the carbon material 10 with an inner peripheral side O-ring 8 attached to the wall surface of the recess of the gas inlet plate 61. The gas inlet plate 61 and the gas outlet plate 62 are in close contact with each other via an outer peripheral side O-ring 9, and the internal space of the recess is sealed. A predetermined pressure is applied with room temperature nitrogen gas from a gas inlet port 71 provided in the center of the gas inlet plate 61. At this time, the flow rate V (L / min) of the nitrogen gas that passes through the inside of the 11 mm-thick carbon material 10 from the inside surface of the inner circumferential O-ring 8 of the carbon material 10 and is discharged from the gas discharge port 72 provided in the center of the gas discharge side plate 62 is measured. Then, the flow rate V (L / min) of the nitrogen gas that passes through the inside of the 11 mm-thick carbon material 10 from the gas discharge port 72 provided in the center of the gas discharge side plate 62 is measured using the following formula (1): 2 Calculate the gas permeation rate X (L / min) per unit. X=0.01V / S …(1) Here, S is the inner surface area of the inner O-ring 8 (m 2 ) However, to ensure measurement accuracy, S is set to 0.005 m. 2 That is all.
[0044] Here, a plate-shaped material with a size of 98 mm × 127 mm × 11 mm was used as a carbon material sample for gas permeability evaluation, and the inner surface area S of the inner O-ring 8 was 0.006 m 2The nitrogen gas pressure was set to four levels of gauge pressure: 50 kPa, 100 kPa, 150 kPa, and 200 kPa, and measurements were carried out at room temperature (23°C). The results are shown in Table 1. Materials with the above gas permeability X of 5 L / min or more and 30 L / min or less at a pressure of 200 kPa were designated as "materials subject to the invention."
[0045] [Table 1]
[0046] From these blocks of carbon material, sheets of carbon material with thicknesses of 1.0 mm and 2.0 mm were made using a milling machine. These were used to make heat dissipation components, and their durability when subjected to a heat cycle was examined. The test results are shown below.
[0047] (1) Testing of the heat dissipation base alone obtained by the molten metal joining method Using a carbon mold with a cross-sectional structure shown in Figure 3, a laminated heat dissipation base was produced by the method described in "Molten metal joining method (1)" above, in which an aluminum-based material was joined to both sides of a carbon material plate. Here, the aluminum-based material was pure aluminum with a purity of 99.9% or more. The pressure of the molten metal by nitrogen gas was about 100 kPa. The edges of the carbon material protruding from the metal material were cut off and removed, and the surface was mechanically polished. The size of the obtained heat dissipation base was 70 mm x 70 mm x t (t is thickness), and the metal materials on both sides of the carbon material were separated. In the projected area viewed in the stacking direction, the area ratio of the carbon material-containing area in the area where the metal materials on both sides of the carbon material overlap was 100%. The type of carbon material used (carbon material No. shown in Table 1) and the thickness of each layer constituting the heat dissipation base are shown in Table 2. Through holes with a diameter of 6 mm were machined at the four corners of this heat dissipation base, and electroless Ni-P plating (medium phosphorus type, plating film thickness 5 μm) was applied to the surface of the heat dissipation base to obtain heat dissipation base products corresponding to the heat dissipation members (specimens) of Examples No. 1 to 8 in Table 2.
[0048] Figure 8 shows a schematic cross-sectional structure of the cross section including the through hole of the obtained heat dissipating base product. Reference numeral 80 denotes a through hole, and reference numeral 81 denotes a plating layer. Reference numerals M1, C, and M2 correspond to the layers listed in Table 2. The thickness of each layer in the stacking direction (z-axis direction) and the thickness of the plating layer are exaggerated (similarly in Figures 9 to 11 described later). The following heat cycle test was carried out on the test specimens made of these heat dissipating base products.
[0049] (Heat cycle test method) The heat dissipation member as a specimen was placed in a heat cycle test chamber and subjected to 1000 cycles of heat cycle testing in the air. The heat pattern for one cycle was as follows: Heat pattern for one cycle: → Hold at -40℃ for 30 minutes → Hold at 25℃ for 10 minutes → Hold at 150℃ for 30 minutes → Hold at 25℃ for 10 minutes
[0050] The thermal conductivity of the heat dissipation base after the electroless plating was completed and the heat dissipation base product after 1000 cycles of the heat cycle test was measured by the following method.
[0051] (Method of measuring thermal conductivity) As shown in FIG. 12(a), a microheater 90, which is a heating element, is attached to the upper surface of a heat dissipation base 100 including a carbon material 10 via a silver-containing thermal conductive grease 85 having a thermal conductivity of 20 W / m·K. FIG. 12(b) is a plan view of the area of the heat dissipation base 100 as viewed from the microheater 90 attachment surface (surface of the metal material 21). The size of the microheater 90 attachment surface of the heat dissipation base 100 is 70 mm×70 mm, the size of each microheater is 10 mm×10 mm×1.5 mm, and nine microheaters are attached evenly at intervals of 13 mm. A copper water-cooling jacket 400 measuring 200 mm×200 mm×20 mm is attached to the rear side (metal material 22 side) of the microheater 90 attachment surface of the heat dissipation base 100 via a silver-containing thermal conductive grease 86 having a thermal conductivity of 20 W / m·K by bolts 87 at the four corners. The thickness of each of the thermal conductive greases 85 and 86 is about 0.5 mm. On both sides of the heat dissipation base 100, the exposed metal wires of the sheathed thermocouples 91 and 92 with an outer diameter of 0.5 mm are attached with Kapton (registered trademark) tape at the position directly under the center of the central microheater (the surface of the metal material 21) and at the rear position in the z-axis direction (the surface of the metal material 22). The sheathed thermocouples 91 and 92 are led out through the layers of the thermal conductive greases 85 and 86, respectively. The types of these sheathed thermocouples are T type and class 1. A current of 100 V and 0.5 A was supplied to each microheater by a DC stabilized power supply device, and heat was generated with an output of 50 W (total output of 9 units is 450 W). Water controlled to 15°C ± 0.2°C by a temperature regulator using a chiller was flowed at a flow rate of 5 L / min into the copper water-cooling jacket 400. After the temperatures measured by the sheathed thermocouples 91 and 92 have both reached a steady state, record the respective measured temperatures as the heat-generating side surface temperature T1 (°C) and the heat-dissipating side surface temperature T2 (°C). The thermal conductivity TC (W / m K) in the lamination direction of the heat dissipating base is calculated using the following formula (2). TC (W / m K) = [total heat output of heater 450 W / total area of heater 0.0009 m 2 ] × [Thickness of heat dissipation base (m) / (T1 (℃) - T2 (℃))] … (2) In FIG. 12, the thickness of each layer in the z-axis direction is exaggerated, and the plating layers are omitted.
[0052] The results are shown in Table 2. The smaller the change in thermal conductivity between the initial state (before the test) and after 1000 cycles of the heat cycle test, the more excellent the durability against heat cycles can be evaluated.
[0053] (2) Testing the heat sink base alone obtained by soldering Using the method shown in Figure 6 described in the "Brazing method" above, a heat dissipation base with a laminated structure was produced in which pure aluminum (purity 99.9% or more) plates were bonded to both sides of a carbon material plate. The aluminum plates on both sides of the carbon material were of the same material. A film of a brazing material component element (Si) was previously deposited by sputtering on the surface of each aluminum plate that was to be bonded to the carbon material. The deposition amount of the brazing material component element was approximately 0.5 mg / cm. 2 The load was applied uniformly in the stacking direction (z-axis direction shown in Fig. 6) so that the surface pressure at the stacking interface was 2 MPa. -5 The heat dissipation base was heated and held at 640°C for 40 minutes under reduced pressure of 10 Pa, and then slowly cooled. The size of the obtained heat dissipation base was 70 mm x 70 mm x t (t is thickness), and the metal materials on both sides of the carbon material were separated, and the area ratio of the carbon material-containing area in the area where the metal materials on both sides of the carbon material overlap in the projected area viewed in the stacking direction was 100%. The type of carbon material used (carbon material No. shown in Table 1) and the thickness of each layer constituting the heat dissipation base are shown in Table 2. Through holes with a diameter of 6 mm were made by machining at the four corners of this heat dissipation base, and electroless Ni-P plating (medium phosphorus type, plating thickness 5 μm) was applied to the surface of the heat dissipation base to obtain heat dissipation members (specimens) of examples No. 9 and 10 in Table 2. The component elements of the brazing material used are shown in Table 2. The cross-sectional structure of the obtained heat dissipation base product was the same as that of (1) above (see Figure 8).
[0054] Heat-dissipating members (specimens) made of these heat-dissipating base products were subjected to a heat cycle test in the same manner as in (1) above, and the change in thermal conductivity before and after the heat cycle test was examined. The results are shown in Table 2.
[0055] [Table 2]
[0056] As can be seen from Table 2, the changes in thermal conductivity before and after the heat cycle test were very small for each example according to the present invention, and the products had excellent durability. In contrast, the thermal conductivity of the comparative example was significantly reduced by the heat cycle. It was confirmed that the reduction in thermal conductivity was due to peeling at the "metal-carbon bonding interface."
[0057] (3) Testing of a heat dissipation component consisting of a heat dissipation base obtained by the molten metal bonding method and an aluminum-clad ceramic circuit board An aluminum-clad ceramic circuit board was fabricated as follows. (Method of manufacturing aluminum-clad ceramic circuit boards) An AlN plate of 50 mm×50 mm×0.635 mm was prepared. In the method described in the above-mentioned "Molten Metal Bonding Method (1)", the above-mentioned AlN plate was used instead of the carbon material to obtain a laminated structure in which pure aluminum (purity 99.9% or more) was bonded to both sides of the AlN plate in a plate shape. After polishing the aluminum surface of the obtained laminated structure, in order to form a circuit pattern (circuit metal plate) and a heat dissipation side metal plate, a predetermined portion was masked, and then an etching solution of iron chloride was sprayed to dissolve and remove a part of the aluminum on the surface of the AlN substrate, and then electroless Ni-P plating was applied to the aluminum surface. In this way, an "aluminum-clad ceramic circuit board" was produced in which aluminum plates of 48 mm×48 mm×0.4 mm were attached to both sides of an AlN plate of 50 mm×50 mm×0.635 mm.
[0058] A heat dissipation base product produced by applying the aluminum-based metal material shown in Table 3 in the same manner as in (1) above and an aluminum-clad ceramic circuit board produced as described above were joined by silver sintering or soldering with lead-free solder (Sn-3Ag-0.5Cu) under a nitrogen atmosphere to obtain heat dissipation members (specimens) corresponding to Examples No. 21, 22, and 24 to 33 in Table 3. For comparison, a heat dissipation base made of a pure aluminum single plate with a thickness of 4 mm that does not use a carbon material and an aluminum-clad ceramic circuit board were joined by silver sintering under a nitrogen atmosphere to obtain a heat dissipation member (specimen) corresponding to Example No. 23 in Table 3. The heat dissipation base product used for silver sintering was electrolessly plated with Au in addition to electrolessly plated with Ni-P.
[0059] Figure 9 shows a schematic cross-sectional structure of the obtained heat dissipation member (specimen). The cross section of the heat dissipation base portion is shown including a through hole 80. The symbols M1, AlN, M2, B, M3, C, and M4 correspond to the layers listed in Table 3. The symbol 50 is a bonding metal layer (a layer derived from silver sintering or a solder layer).
[0060] A heat cycle test was performed on these heat dissipation members (specimens) in the same manner as in (1) above, and the change in thermal resistance (between M1 surface and M4 surface) before and after the heat cycle test was examined. The thermal resistance of the heat dissipation members before and after the heat cycle test was measured as follows.
[0061] (Method of measuring thermal resistance) As shown in Fig. 13(a), a microheater 90, which is a heating element, is attached to the top surface of a heat dissipation member, a specimen 500 (the specimen illustrated in this figure is a laminated structure with reference numbers 22 to 41), via silver-containing thermal conductive grease 85 with a thermal conductivity of 20 W / m K. (b) is a plan view of the area of the specimen 500, as seen from the side where the microheater 90 is attached. The size of the microheater 90 attachment surface of the specimen 500 (the surface of the metal material 41 for circuits in the example of this figure) is 48 mm x 48 mm, each microheater is 10 mm x 10 mm x 1.5 mm, and four microheaters are attached evenly spaced 15 mm apart. A copper water-cooling jacket 400 measuring 200 mm x 200 mm x 20 mm is attached to the rear side of the mounting surface of the microheater 90 of the specimen 500 (the side of the metal material 22 in the example of this figure) by bolts 87 via silver-containing thermal conductive grease 86 with a thermal conductivity of 20 W / m·K. The thickness of each of the thermal conductive greases 85 and 86 is approximately 0.5 mm. On both the upper and lower surfaces of the specimen 500, the exposed metal wires of the sheathed thermocouples 91 and 92 with an outer diameter of 0.5 mm are attached with Kapton (registered trademark) tape at a position directly under the center of one of the microheaters (the surface of the metal material 41 for the circuit in the example of this figure) and at the rear position in the z-axis direction (the surface of the metal material 22 in the example of this figure), and the sheathed thermocouples 91 and 92 are led out through the layers of thermal conductive grease 85 and 86, respectively. The type of these sheathed thermocouples is T type, class 1. A current of 100V 0.5A was supplied to each micro-heater by a DC stabilized power supply, and heat was generated at an output of 50W (total output of 4 units was 200W). Water controlled to 15°C ± 0.2°C by a temperature regulator using a chiller was flowed through the copper water-cooling jacket 400 at a flow rate of 5L / min. After the temperatures measured by the sheathed thermocouples 91 and 92 both reached a steady state, the respective measured temperatures were recorded as the heat generation side surface temperature T1 (°C) and the heat dissipation side surface temperature T2 (°C). The thermal resistance R (K / W) in the layering direction of the specimen was calculated using the following formula (3). R(K / W)=(T1(℃)-T2(℃)) / total heat output of heater 200W …(3) In FIG. 13, the thickness of each layer in the z-axis direction is exaggerated, and the plating layers are omitted.
[0062] The results are shown in Table 3. The smaller the change in thermal resistance between the initial state (before the test) and after 1000 cycles of the heat cycle test, the more excellent the durability against heat cycles can be evaluated.
[0063] [Table 3]
[0064] As can be seen from Table 3, the changes in thermal resistance before and after the heat cycle test were very small for each of the examples according to the present invention, and the products had excellent durability. In contrast, the thermal resistance of the comparative examples increased significantly when subjected to a heat cycle. It was confirmed that the increase in thermal resistance was caused by peeling of the "metal-carbon bonding interface" and cracks in the silver sintering layer or solder layer. In No. 23, which did not use a carbon material, the thermal resistance increased significantly due to peeling of the silver sintering layer.
[0065] (4) Testing of a heat sink component consisting of a heat sink base obtained by soldering and an aluminum-clad ceramic circuit board A heat dissipating base product produced by the same method as in (2) above and an aluminum-clad ceramic circuit board produced by the method described in (3) above were joined by lead-free soldering in a nitrogen atmosphere to obtain heat dissipating components (specimens) corresponding to Examples No. 34 to 47 in Table 4. However, in the examples (No. 42 to 47) in which a copper-based metal material was used in the production of the heat dissipating base product, the heating temperature during brazing was set to 850°C. The component elements of the brazing material used are listed in Table 4. The cross-sectional structure of the obtained heat dissipating components (specimens) was the same as that produced in (3) above (see Figure 9).
[0066] The change in thermal resistance (between M1 surface and M4 surface) of these heat dissipation members (specimens) before and after the heat cycle test was examined using the same method as in (3) above. The results are shown in Table 4.
[0067] [Table 4]
[0068] As can be seen from Table 4, the changes in thermal resistance before and after the heat cycle test were very small for each example according to the present invention, and the products had excellent durability. In contrast, the thermal resistance of the comparative example increased significantly when subjected to a heat cycle. It was confirmed that the increase in thermal resistance was due to peeling at the "metal-carbon bonding interface" and cracks in the solder layer.
[0069] (5) Testing of base-integrated insulated circuit boards obtained by the molten metal bonding method Using a carbon mold with a cross-sectional structure shown in Figure 4, a "base-integrated insulating circuit board" having a laminated structure in which an aluminum-based material and a carbon material are bonded was produced by the method described in "Molten metal bonding method (2)" above. An AlN plate with a size of 50 mm x 50 mm x 0.635 mm was used as the ceramic material. The pressure of the molten metal by nitrogen gas was about 100 kPa. The edge of the carbon material protruding from the metal material was cut and removed, and the surface of the aluminum-based material was mechanically polished. In order to remove unnecessary aluminum-based material covering the end of the AlN plate, a specified portion was masked and then an iron chloride aqueous solution was sprayed to dissolve and remove part of the aluminum-based material on the AlN surface, and then the masking was peeled off with a chemical solution. In the obtained base-integrated insulating circuit board, the metal materials on both sides of the carbon material were separated, and the area ratio of the carbon material-existing area in the area where the metal materials on both sides of the carbon material overlap in the projected area viewed in the stacking direction is 100%. The type of carbon material used (carbon material number shown in Table 1), the type of aluminum-based material used, and the thickness of each layer constituting the "base-integrated insulating circuit board" are shown in Table 5. Through holes with a diameter of 6 mm were made by machining in the four corners of this base-integrated insulating circuit board, and electroless Ni-P plating (medium phosphorus type, plating thickness 5 μm) was applied to the surface except for the parts where the ceramic (AlN) was exposed, to obtain base-integrated insulating circuit board products corresponding to the heat dissipation members (specimens) of Examples Nos. 61 to 74 in Table 5.
[0070] FIG. 10 shows a schematic cross-sectional structure of a heat dissipation member (specimen) made of the obtained base-integrated insulating circuit board product. Here, the ceramic material 30 is an AlN plate. Reference numeral 10 denotes a carbon material, and the dimensions of the heat dissipation base portion (laminated portion made of reference numerals 21, 10, and 22) as viewed in the lamination direction (z-axis direction) are 70 mm x 70 mm. The cross section of the heat dissipation base portion including a through hole 80 is shown. Reference numeral 81 denotes a plating layer. Reference numerals M1, AlN, M2, C, and M3 correspond to the layers listed in Table 5.
[0071] The change in thermal resistance (between M1 surface and M3 surface) of these heat dissipation members (specimens) before and after the heat cycle test was examined using the same method as in (3) above. The results are shown in Table 5.
[0072] [Table 5]
[0073] (6) Testing of base-integrated insulated circuit boards obtained by soldering An aluminum plate (purity 99.9% or higher) measuring 48 mm × 48 mm × 0.3 mm and an AlN plate measuring 50 mm × 50 mm × 0.635 mm were prepared, and brazing material component element (Si) was sputtered on one side of the aluminum plate at approximately 0.5 mg / cm. 2 The brazing material component was deposited in an amount of 1000g. The aluminum plate-AlN plate-aluminum plate were laminated on top of an alumina plate spacer in this order, so that the brazing material component-deposited surface of the aluminum plate was in contact with the AlN surface. On top of that, multiple laminated structures of aluminum plate-AlN plate-aluminum plate similar to the above were further stacked on top of that, with spacers between them, and a spacer was also placed on the top. The laminate thus obtained was subjected to a load evenly applied in the lamination direction so that the surface pressure at the lamination interface was 2 MPa, and then it was subjected to a load of 1000g. -5 The laminated structure was heated and held at 640°C for 40 minutes under a reduced pressure of 10 Pa, and then slowly cooled to obtain a laminated structure in which an aluminum plate, an AlN plate, and an aluminum plate were bonded together. The surface of the aluminum plate in this laminated structure was polished, and then, for the purpose of forming a circuit pattern (circuit metal plate) and a heat dissipation side metal plate, predetermined areas were masked and then an etching solution of iron chloride was sprayed to dissolve and remove some of the aluminum on the surface of the AlN substrate, and electroless Ni-P plating was applied to the surface of the aluminum-based material to produce an aluminum-clad ceramic circuit board.
[0074] FIG. 11 shows a schematic cross-sectional structure of a heat dissipation member (specimen) made of a base-integrated insulating circuit board fabricated by the brazing method. Here, the ceramic material 30 is an AlN plate, the circuit metal material 41 and the heat dissipation side metal material 42 are aluminum-based material plates, and the laminated portion of the reference numbers 41, 30, and 42 corresponds to the aluminum-clad ceramic circuit board. Reference number 10 is a carbon material plate, the metal materials 21 and 22 are aluminum-based material plates, and the laminated portion of the reference numbers 21, 10, and 22 corresponds to the heat dissipation base. Here, an aluminum (purity 99.9% or more, thickness 0.3 mm) plate material 83 is further joined by brazing on the aluminum-clad ceramic circuit board. In addition, a peripheral wall portion 82 made of an aluminum block (purity 99.9% or more, thickness 1.535 mm) is installed by brazing.
[0075] In the brazing process, elements of brazing material components are previously sputtered at a rate of about 0.5 g / cm onto one side surface of the aluminum-based material plate 83, the surface of the aluminum-based plate 42 constituting the aluminum-clad ceramic circuit board, one side surfaces of the aluminum-based material plates 21 and 22 to be joined to the carbon material 10, and the lower surface of the aluminum-based material constituting the peripheral wall portion 82. 2 The aluminum-based material constituting the plate material, the aluminum-clad ceramic circuit board, and the peripheral wall portion 82 were laminated in the arrangement shown in FIG. 11, and a load was applied via a ceramic plate-shaped spacer in the lamination direction (z-axis direction shown in FIG. 11) so that the average surface pressure of the carbon material surface was 2 MPa. -5The brazing was performed by heating and holding at 640°C for 40 minutes under a reduced pressure of 100 Pa, and then slowly cooling. The aluminum-based material plates designated by the reference numerals 83, 21, and 22 had the same composition. The brazing material components were common to each part. The type of carbon material used (carbon material No. shown in Table 1), the type of aluminum-based material used by the reference numerals 83, 21, and 22, the elements of the brazing material components, and the thickness of each layer constituting the "base-integrated insulating circuit board" are shown in Table 5. Through holes 80 with a diameter of 6 mm were formed by machining at the four corner positions penetrating the peripheral wall portion 82 of this base-integrated insulating circuit board, and electroless Ni-P plating (medium phosphorus type, plating thickness 5 μm) was applied to the surface except for the part where the ceramic (AlN) was exposed, to obtain a base-integrated insulating circuit board product corresponding to the heat dissipation member (specimen) of Example Nos. 75 to 82 in Table 5. The dimensions of the heat dissipation base part (laminated part consisting of reference numbers 21, 10, and 22) as viewed in the lamination direction (z-axis direction) are 70 mm x 70 mm. The cross section of the heat dissipation base part including a through hole 80 is shown. Reference number 81 is a plating layer. Reference numbers M1, AlN, M2, M3, C, and M4 correspond to the layers listed in Table 6.
[0076] The change in thermal resistance (between M1 surface and M4 surface) of these heat dissipation members (specimens) before and after the heat cycle test was examined using the same method as in (3) above. The results are shown in Table 6.
[0077] [Table 6]
[0078] As can be seen from Tables 5 and 6, the changes in thermal resistance before and after the heat cycle test were very small for each example according to the present invention, and the products had excellent durability. In contrast, the thermal resistance of the comparative example increased significantly when subjected to the heat cycle. It was confirmed that the increase in thermal resistance was due to peeling of the "metal-carbon bonding interface." [Explanation of symbols]
[0079] 1. Mold 1a Upper mold member 1b Lower mold member 2 Molten metal 3 Cover member 4 Pouring spout 5 Spacer 8 Inner O-ring 9 Outer O-ring 10 Carbon Materials 21, 22 Metal materials 30 Ceramic Materials 41 Metal materials for circuits 42 Heat dissipation metal material 50 Bonding metal layer 51 Molten metal storage section 52 Molten metal supply line 53 Fin forming recess 61 Gas inlet plate 62 Gas exhaust side plate 71 Gas inlet 72 Gas exhaust port 80 through hole 81 Plating layer 82 Peripheral wall section 83 Aluminum-based material sheets 85, 86 Thermal grease 87 Volts 90 Micro Heater 91, 92 Sheathed thermocouple 100 Heat dissipation base 101 Laminate 200, 300 Insulated circuit board 400 Water Cooling Jacket 500 specimens
Claims
1. A method for manufacturing a heat dissipation member, comprising the steps of: injecting molten aluminum or an aluminum alloy at a pressure of 30 to 200 kPa into a mold in which a carbon material having the properties shown in (A) below (excluding a composite material in which a carbonaceous member is filled with a metal) is placed, filling the space in the mold with the molten metal, and then solidifying the molten metal to form a laminated structure in which a metal material made of aluminum or an aluminum alloy and the carbon material are bonded together. (A) When a pressure of 200 kPa of nitrogen gas is applied to one main surface of a plate-shaped sample having a thickness of 11 mm and made of the carbon material, the flow rate of the nitrogen gas permeating to the other main surface side is 0.01 m2 or less per an area of the main surface being pressurized. 2 A carbon material with a gas permeability of 5 L / min to 30 L / min per unit area, provided that the area of the main surface to be pressurized is 0.005 m 2 That is all.
2. The method for producing a heat dissipation member according to claim 1 , wherein the carbon material has a bending strength of 40 MPa or more.
Citation Information
Patent Citations
Metal-ceramics composite material and its manufacture
JP2000336438A
Metal / ceramic joined substrate
JP2006282417A
Heatsink material and its manufacturing method
JP2006298687A
Aluminum-graphite composite, circuit board using it, and manufacturing method therefor
JP2010029919A
Substrate for power module with heat sink, power module with heat sink and substrate for power module with buffer layer
JP2010098057A
Cited By
Aluminum composite material and method for manufacturing the same
JP7884889B1